Reorienting Oral Health Services to Prevention: Economic Perspectives. (June 2021) - Vernazza, C.R.; Birch, S.; Pitts, N.B.
Despite the recognized need to change the emphasis of health services by shifting the balance from treatment to prevention, limited progress has been made in many settings. This is true in oral health, where evidence for preventive interventions that work has not been systematically exploited in oral health services. While reorienting health services is complex and context specific, economics can bring a helpful perspective in understanding and predicting the impact of changes in resource allocation, provider remuneration systems, and patient payments. There is an increasing literature on the economics of different prevention approaches. However, much of this literature focuses on the costs and potential savings of alternative approaches and fails to take into account benefits. Even where benefits are taken into account, these tend to be narrowly focused on clinical outcomes using cost-effectiveness analysis, which may be of little relevance to the policy maker, patient, and the public. Some commonly used economic approaches (such as quality-adjusted life years and incremental cost-effectiveness ratios) may also not be appropriate to oral health. Using alternative techniques, including wider measures of benefit and employing priority setting and resource allocation tools, may provide more comprehensive information on economic impact to decision makers and stakeholders. In addition, it is important to consider the effects of provider remuneration in reorienting services. While there is some evidence about traditional models of remuneration (fee for service and capitation), less is known about pay for performance and blended systems. This article outlines areas in which economics can offer an insight into reorientation of health systems toward prevention, highlighting areas for further research and consideration.